Will tourism cultural experience affect tourist citizenship behaviors? A case of the “Village Basketball League” in Taijiang County, Guizhou Province - Yuxin Yang; Yuting Lin; Chen Qiu; Youcheng Chen; Shuisheng Fan; Zhidan Chen; Yongqiang Ma (PLoS ONE, 2025)
In the era of the experience economy, the tourist experience has become a key factor in the development of tourist destinations. Unlike traditional sightseeing experiences, tourism cultural experiences allow for engagement in cultural activities at the destination, thereby fostering a deeper emotional connection with the local community, which subsequently influences tourists’ citizenship behavior. The “Village Basketball League” in Taijiang County, Guizhou Province is characterized as a form of tourism cultural experience with high integration and strong involvement. This study presents the “Village Basketball League” in Taijiang County as a case study. Grounded in SOR (Stimuli-Organism-Response) theory and involvement theory, this study explores the influencing factors of tourist citizenship behaviors from the perspective of the integration of culture and sports and constructs a structural equation model that includes tourism cultural experience, tourists’ involvement, flow experience, and tourist citizenship behaviors. Data analysis was performed using SmartPLS 4.0 on questionnaires completed by 314 tourists. The results indicate that: (1) The tourism cultural experience positively affects tourist feedback behaviors, tourist recommendation behaviors, and flow experience; (2) Flow experience positively influences tourist feedback behaviors and recommendation behaviors; (3) Flow experience serves as a mediator between the tourism cultural experience and both tourist feedback behaviors and tourist recommendation behaviors; (4) Tourists’ involvement negatively moderates the predictive effect of tourism cultural experience on flow experience. The research findings offer valuable insights for decision-making regarding the development of tourism destinations and offer guidance for tourism development and management.